Gender and perspectives on training and techniques: analyses of the system of attacks in standing up position - Calmet, M.; Pierantozzi, E. (The Arts and Sciences of Judo, 2021)
The concept of a system of attacks explains how a judoka throws opponents during a contest; it integrates favorite throws, organized with specific kumi-kata (gripping) and can evolve throughout practice. Criteria defining it are: type of kumi-kata, time of triggered attack, name of throw, direction of attack, number of points of contact with the ground during the throw, scored attack. Calculated criteria are: sum of contest duration, rate of attacks, use of kumi-kata, linked attacks, efficient sectors. 28 high-level judoka, from 9 countries, who did at least 4 contests in the same high-level competition were analyzed. Results show no difference between women and men concerning: number of contests, sum of contest duration, number of kumi-kata used, total number of attacks, number of directions of attacks, number of attacks with either one foot, two feet or back-side in contact with the mat, rate of attacks for 30s, percentage of linked attacks, percentage of attacks with kumi-kata corresponding to the direction of attack, percentage of attacks with kumi-kata opposed to the direction of attack, percentage of attacks with mixed kumi-kata, number of attacks scored. There was a difference between women and men concerning efficient sectors of attacks (2.2±1.1 vs 2.8±0.9 respectively, p=0.004). ANOVA confirms sample cohesion; shows champions` organization and highlights different profiles. Rules suggest that number of contests, sum of contest duration and total number of attacks can be identical for women and men respectively. However, number of kumi-katas, number of directions of attacks, rate of attacks, use of kumi-kata and efficiency, show that women and men practice judo with the same efficiency.